2019
DOI: 10.1155/2019/9856734
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Carbonation Resistance of Portland Cement Mortar Incorporating γ-Dicalcium Silicate

Abstract: In this study, γ-dicalcium silicate (γ-C2S) was incorporated into ordinary Portland cement (OPC) to sequester CO2 to enhance the carbonation resistance of cement-based composite materials. γ-C2S can react with CO2 rapidly to form vaterite and high dense SiO2 gel which could block the pores off and then inhibit further diffusion of CO2 into the system. Cement mortar specimens containing 0%, 5%, 10%, 20%, and 40% γ-C2S as cement replacement were prepared. After water curing for 28 days followed by curing in an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Because the aged paste samples had been dried at 105 °C for 6 h prior to TG-DTG analysis, the amount of interlayer water in the dried test paste samples was small. In consequence, the mass It should be noted that the spectral region 1422-1440 cm −1 belonged to asymmetric stretching υ 3 CO 3 2− from amorphous CaCO 3 [53], and the absorption peaks at 875 cm −1 assigned to the out-of-plane bending of υ 2 C-O from calcite and vaterite [54]. The curing environment of the composite pastes met all the requirements of mineral carbonation [13].…”
Section: Hydration Productsmentioning
confidence: 88%
See 2 more Smart Citations
“…Because the aged paste samples had been dried at 105 °C for 6 h prior to TG-DTG analysis, the amount of interlayer water in the dried test paste samples was small. In consequence, the mass It should be noted that the spectral region 1422-1440 cm −1 belonged to asymmetric stretching υ 3 CO 3 2− from amorphous CaCO 3 [53], and the absorption peaks at 875 cm −1 assigned to the out-of-plane bending of υ 2 C-O from calcite and vaterite [54]. The curing environment of the composite pastes met all the requirements of mineral carbonation [13].…”
Section: Hydration Productsmentioning
confidence: 88%
“…It can be concluded that during the pastes' hydration curing, the moisture not only participated in the mineral hydration reaction, but also transformed into interlayer water, which cannot be removed completely at 105 °C . It should be noted that the spectral region 1422-1440 cm −1 belonged to asymmetric stretching υ3 CO3 2− from amorphous CaCO3 [53], and the absorption peaks at 875 cm −1 assigned to the out-of-plane bending of υ2 C-O from calcite and vaterite [54]. The curing environment of the composite pastes met all the requirements of mineral carbonation [13].…”
Section: Hydration Productsmentioning
confidence: 88%
See 1 more Smart Citation
“…Earlier studies also reported lower average pore size in case of CNT, NCC, MCC and CNT-MCC hierarchical composites (Parveen et al 2015(Parveen et al , 2017b(Parveen et al , 2018Alshaghel et al 2018;Silva et al 2018;Wang et al 2020). While due to their nano-sized structure CNTs could reduce pore size of cementitious composites by their pore-filling effect (Parveen et al 2015;Chen et al 2019), the formation of higher amount of hydration products was the main reason behind improved microstructure of MCC based composites (Parveen et al 2017b(Parveen et al , 2018. In spite of reduced pore size, an increase in the overall porosity was previously noticed in MCC based composites due to MCC agglomeration (Parveen et al 2017b(Parveen et al , 2018.…”
Section: Hydration Behavior Of Plain Mortar and Cementitious Compositesmentioning
confidence: 91%
“…An increase in MCC concentration increased MCC agglomeration and therefore, reduced the favorable effects of MCC addition. Lower carbonation of hierarchical composites is expected to enhance their durability as carbonation is a potential cause of corrosion of steel reinforcements and resulting deterioration of concrete's mechanical properties (Chen et al 2019). XRD analysis of plain mortar and selected hierarchical cementitious composite (0.1% MCC ?…”
Section: Hydration Behavior Of Plain Mortar and Cementitious Compositesmentioning
confidence: 99%